INOVASI PEMBELAJARAN BAHASA INDONESIA MELALUI PENDEKATAN PROSES - Umar Mansyur (Universitas Negeri Makassar, 2016)
Abstract: Indonesian Learning Innovation through Process Approach. Today there are many teachers who use the technique theoretically and rote learning, so learning activities tend to be rigid, monotonous, and boring. Especially in the Indonesian language teaching, the material presented in fact they could not rub off on students as rational, cognitive, and affective. The use of conventional learning methods still that which impact on the level of mastery of the subject matter Indonesian students still low. Furthermore, the condition of this kind of learning is a form of failure of students in developing knowledge and language skills, and positive attitudes toward the use of the Indonesian language is good and true. Conditions like these can be addressed by implementing learning innovations that can be used by teachers in implementing the Indonesian language learning through a process approach, embodied in four aspects of Indonesian language skills, ie skills of listening, speaking, reading, and writing.